Assessment of heart rate complexity recovery from maximal exercise using recurrence quantification analysis - Hoshi, Rosangela Akemi; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Godoy, Moacir Fernandes (Springer Nature, 2016)
Recurrence Plots have been described as suitable method for nonstationary and short data analysis, however, up to date, there is no registered study using this technique to evaluate exercise and recovery, which are conditions that provide unstable and variable heart rate time series. Objectives: To analyze heart rate complexity of healthy and young subjects during recovery from maximal exercise, using RQA measurements. Methods: Twenty participants were submitted to 120 min of passive recovery assessment after exercise at 100 % of maximal velocity until exhaustion. HR and R-R intervals (RRi) were recorded during the whole process and segments containing 300 RRi were selected from the baseline period and at each 10 min of recovery to be analyzed by the Kubios HRV Analysis software. Results: At baseline, the median values of Recurrence Rate, Determinism, Entropy and Lmean were 25.1 %, 97.2 %, 2.9 % and 8.6 %, respectively. After the exercise, all these variables showed significant increase until 80 min. Then, from 90 min and onwards, no significant difference was found between recovery moments and baseline. Conclusions: The regularity of heart rate rhythm increases expressively after maximal exercise and the complexity reduces. During recovery period, these conditions gradually return to rest levels and reach recovery after 80 min. As the variables showed pre-exercise levels at a similar moment, RQA seems to be a suitable method to evaluate exercise and recovery conditions.